Invasive Pneumococcal Infections in Children with Nephrotic Syndrome in Bangladesh. Issue 8 (August 2019) - Malaker, Roly; Saha, Senjuti; Hanif, Mohammed; Ahmed, ASMNU; Saha, Shampa; Hasanuzzaman, Md.; Khondakar, Tarannum; Islam, Maksuda; Baqui, Abdullah H.; Santosham, Mathuram; Darmstadt, Gary L.; Whitney, Cynthia G.; et al.
Abstract : Introduction: Children with nephrotic syndrome are susceptible to invasive bacterial infections. In this study, we aimed to: (1) determine the pathogens associated with infections in children with nephrotic syndrome and (2) describe antimicrobial susceptibility and serotype distribution of Streptococcus pneumoniae to guide evidence-based treatment and prevention policies. Methods: From June 2013 to March 2015, we collected blood and/or ascitic fluid from children hospitalized with nephrotic syndrome and suspected bacterial disease in the largest pediatric hospital of Bangladesh. We cultured all samples and performed polymerase chain reaction (PCR) and immunochromatographic test on ascitic fluid for detection of S. pneumoniae . Pneumococcal isolates were tested for antibiotic susceptibility using disc diffusion and serotyped using Quellung reaction and PCR. Results: We identified 1342 children hospitalized with nephrotic syndrome. Among them, 608 children had suspected bacterial disease from whom blood and/or ascitic fluid were collected. A pathogen was identified in 8% (48/608) of cases, 94% (45/48) of which were S. pneumoniae . Most (73%, 33/45) pneumococcal infections were identified through culture of blood and ascitic fluid and 27% (12/45) through immunochromatographic test and PCR of ascitic fluid. In total, 24 different pneumococcal serotypes were detected; 51% are covered by PCV10 (+6A), 53% by PCV13 and 60% by PPSV23. All pneumococcal isolates were susceptible to penicillin. Conclusions: Because S. pneumoniae was the primary cause of invasive infections, pneumococcal vaccines may be considered as a preventive intervention in children with nephrotic syndrome. Additionally, penicillin can be used to prevent and treat pneumococcal infections in children with nephrotic syndrome in Bangladesh. Abstract : Supplemental Digital Content is available in the text.